Ultrasound abdomen as a tool to predict difficult cholecystectomy - Mulla, Sameer Ahmed; Pai, Srinivas; Shetty, Dishita (International Surgery Journal, 2020)
Background: Laparoscopic cholecystectomy is a commonly performed procedure in general surgical practise, which can sometimes be tedious and can have high morbidity. Ultrasound abdomen is a routinely performed radiological investigation for every case of cholecystectomy. This study intends to find correlation between the ultrasound findings and the perceived difficulty during surgery. Methods: This is a prospective study of 100 patients who underwent cholecystectomy after a preoperative ultrasound. Difficult cholecystectomies were defined and sonographic findings and intraoperative difficulties recorded and tabulated. Results: Fifty one cholecystectomies were classified as difficult cholecystectomy (20 converted to open procedure and 31 took more than 90 min to complete laparoscopically). The commonest ultrasound finding that was encountered was multiple calculi (62%) followed by gallbladder (GB) wall thickness of >4 mm (33%), stone size >1 cm (22%), contracted GB (17%), intrahepatic biliary radicals (IHBR) dilatation (15%) and the least common finding was empyema of the gallbladder seen in 7% of the cases. Conclusions: This study is a reflection of surgeries performed by a single team over 3 years which included 100 cases. It was started with an idea to identify the findings on a preoperative ultrasound that predicted a difficult cholecystectomy (laparoscopic or open). In our experience we found that empyema GB, pericholecystic fluid, IHBR dilatation and wall thickness of GB are excellent predictors of a difficult cholecystectomy.